STATUS OF POLLUTANTS IN NSUDU-RIVER, OKWOYI ISIEKE IBEKU UMUAHIA NORTH, LOCAL GOVERNMENT AREA OF ABIA STATE FOR DRINKING PURPOSE - CHIWETALU, Uche Jenice (FUDMA JOURNAL OF SCIENCES, 2021)
This study examines the status of pollutants in Nsudu River for drinking water purpose. Water samples were collected from Nsudu River and analyzed at Enugu State Water Corporation (quality control unit) laboratory. Physical, chemical and bacteriological tests were conducted on the collected samples following standards and acceptable methods of water analysis. The results obtained showed that turbidity, total solid, total suspended solid, total dissolved solid, alkalinity, electrical conductivity, pH, total hardness, calcium, magnesium, iron, chloride, etc. conformed with the acceptable limits stipulated by both World Health Organization (WHO) and Nigerian standard for Drinking Water Quality (NSDWQ) with the exception of the biological parameters which were found to be above the standards stipulated by the two bodies. More so, ANOVA results showed (P < 0.01) and (F-test of 12094 > F-crit. of 6.9) indicating significant difference between the biological contaminants
Keywords: Drinking, Nsudu-River, Pollutants, Status, Water